2014
DOI: 10.5897/ajbm2014.7520
|View full text |Cite
|
Sign up to set email alerts
|

Organizational performance and readiness for change in public sector undertakings

Abstract: The present study makes an assessment of the readiness/resistance to change of employees of State Public Sector Undertakings (SPSUs), compares readiness between executives and workers of SPSUs, employees of SPSUs and Central Public Sector Undertakings (CPSUs), and between employees of Public Sector Undertakings (PSUs) making profits as well as losses. The factors affecting readiness to change were identified from literature. A standard questionnaire was used to explore the factors that contribute to the succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…However, the maladies afflicting Indian PSUs leading to low capacity utilization has been subjected to criticism. Extending this argument to the component level (State level) Mathew, Sulphey & Rajasekar (2014) established that most of the SPSUs in Kerala are poor performers. Reforms are needed to strengthen PSUs that are poorly organized, with irrational decision-making processes, staff mismanaged, weak accountability, poorly designed public programs and poorly delivered public services (Schacter, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the maladies afflicting Indian PSUs leading to low capacity utilization has been subjected to criticism. Extending this argument to the component level (State level) Mathew, Sulphey & Rajasekar (2014) established that most of the SPSUs in Kerala are poor performers. Reforms are needed to strengthen PSUs that are poorly organized, with irrational decision-making processes, staff mismanaged, weak accountability, poorly designed public programs and poorly delivered public services (Schacter, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hal ini sebagaimana diungkapkan oleh Pham & Kim (2019), Singhapakdi et al (1995), Zahra & LaTour (1987). Kesiapan untuk berubah juga menjadi variabel penting dalam percepatan organisasi beradaptasi (Mathew et al, 2014) dan Caliskan & Isik (2016). Hal ini dapat dipahami mengingat kita akan sama-sama menghadapi situasi transisi menuju new normal.…”
unclassified
“…The results revealed that change management improves the performance of selected organizations. In addition, a positive and significant relationship was found between the commitment of top and middle-level management staff and the implementation of change in selected organizations Matthew, Sulphey and Rajasekar (2014). assessed the readiness and resistance to change of employees of state public sector organizations and compared the readiness between executives and employees of state public sector organizations and central public sector organizations in India.…”
mentioning
confidence: 99%